(untitled) (Journal of Brahmanbaria Medical College, 2026)
Background: Congenital Pulmonary Airway Malformation (CPAM) is a rare developmental lung anomaly that may present with respiratory distress in neonates or recurrent respiratory tract infections in older children.This case report aims to describe a case of delayed diagnosis of Congenital Pulmonary Airway Malformation (CPAM) in a 4-year-old child presenting with recurrent pneumonia and to highlight the importance of clinical suspicion, imaging and timely surgical intervention in improving outcomes, particularly in resource-limited settings. Case Presentation: We describe a 4-year-old girl with recurrent chest infections, growth failure, and chest deformity. Clinical evaluation and imaging confirmed CPAM of the right lung. She underwentsurgical lobectomy with favorable recovery. Conclusion: CPAM should be suspected in children with recurrent pneumonia unresponsive to conventional therapy. Early surgical intervention prevents recurrent infections and long-term complications. JBRMC, Volume 08 Issue 01 January 2026 ; 47-49